A CROSS-SECTIONAL STUDY TO ASSESS THE PROBABILITY OF ADVERSE POSTOPERATIVE INCIDENCE AND RELATED FACTORS IN PATIENTS WITH APPENDICITIS.: http://doi.org/10.46536/jpumhs/2024/14.02.524 - Umair Bin Nasir1 , Sahar Mudassar2 , Arooj Javed3 , Ayesha Shahid Butt 4 , Areesha Arif5 , Mudassar Ali6, (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2024)
BACKGROUND: As appendicitis is a surgical emergency, an appendix that is inflamed may need to be removed. The unfavorable outcomes could include perforation, appendicular abscess, and even death if left untreated. OBJECTIVE: In order to explore poor outcomes and associated factors among patients who had appendicitis surgery, this study was carried out. METHODS: A retrospective cross-sectional study was conducted on 121 patients who underwent appendicitis surgery between September 1, 2022, and July 30, 2023. A checklist was used to gather data. For data entry and analysis, Epi-data and SPSS version 25 were utilized, respectively. Utilizing a binary logistic regression model, independent factors were found. The statistical significance of factors was set at p <0.05. RESULTS: Nine patients did not recover fully among the 121 who had surgery for acute appendicitis. Wound infection was the most common postoperative condition, despite one sepsis-related death being reported. CONCLUSION: There was a high risk of an adverse outcome from acute appendicitis in this study. More than 10% of cases of appendicitis resulted in adverse events. A mass in the lower right quadrant, being hospitalized for more than three days, living outside of the hospital setting area, and having a long record of sickness were the risk factors for appendicitis. However, females were less likely to experience negative outcomes from the condition.